Giant cystic malignant pheochromocytoma invading right hepatic lobe: report on two cases - Costa, Sergio Renato Pais; Cabral, Nivaldo Marques; Abhrão, Ademir Torres; Costa, Ricardo Borges da; Silva, Lilian Mary da; Lupinacci, Renato Arioni (São Paulo Medical Journal, 2008)
CONTEXT: Cystic pheochromocytomas are uncommon neuroendocrine tumors that originate from the adrenal medulla. Differing from the more frequent solid pheochromocytomas, which produce catecholamines and present adrenergic syndrome, cystic pheochromocytomas may not produce these. Their symptoms are generally associated with an abdominal mass or even pain, particularly if the mass attains large dimensions. Similarly, radiological diagnosis may also be diffi cult. Right-side lesions may be confounded with cystic hepatic tumors or even retroperitoneal sarcomas with cystic areas, using radiological methods. Sometimes, there may be a preoperative diagnosis of malignancy. Invasion of organs in this region (i.e. liver or kidney), or even the presence of a large retroperitoneal mass (of uncertain origin) with which multiple organs are involved, may be indicative of malignant origin. CASE REPORT: Two cases of giant cystic pheochromocytoma that invaded the right hepatic lobe are described. These presented as abdominal masses. Both cases were malignant. They were treated by radical right nephrectomy plus right hepatectomy.